Peningkatan Kegiatan Dinas Jaga Mesin pada Pengoperasian Mesin Penggerak Utama pada KM. Hasil Melimpah 18 - I Made Aditya Nugraha; Rasdam Rasdam; Resky Amalia Rajab (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Watchkeeping is guard work carried out on ships or in ports to create situations and conditions to be safe and under control for 24 hours carried out with the aim of work affairs in order to create safety and security while on duty. Hasil Melimpah 18 Vessel is classified as a fishing vessel of a special type only to accommodate fish cargo and does not carry out fishing operations. In an effort to achieve the goal of watchkeeping, a study is carried out related to the evaluation of the activities of the watchkeeping in the operation of the machine. From the results of observations, it is necessary to increase the activities of the watchkeeping in the operation of the main engine. This needs to be done to improve the performance before and after the machine is operated, and the watchkeeping when the machine is operating. The increase in the activities of the watchkeeping in the operation of the main engine can be done by several improvements, such as in the preparation, operation, and watchkeeping duty activities. In preparation activities, it is necessary to increase the availability of OHS equipment, logbooks, and spare parts as needed. In operating activities, it is necessary to increase the availability of OHS equipment, communication tools, and electrical panels. In watchkeeping duty activities, it is necessary to increase the availability of the watchkeeping schedule, machine daily journals, and measuring tools. Periodic control while the machine is operating is very important. The watchkeeper must have a big responsibility because machine damage can occur if the duty officer on duty commits negligence.